Losing generations : adolescents in high-risk settings (National Academy Press, 1993)
For millions of adolescents ... the context of their lives is one of meager and uncertain income, dilapidated neighborhoods, inadequate schools, dangerous streets, and violent homes. /// Such environments not only lack the basic support systems [but] are actually dangerous and destructive to young people growing up in them. This volume breaks new ground by exploring these [disadvantaged] settings in which American youth are expected to mature to responsible adulthood. To focus on settings is to recognize that context has a profound influence on the shape of a young person's entire life as well as the day-to-day decisions that result in high-risk behavior. This book recognizes that there are roadblocks that even the most energetic youth cannot overcome. If we expect to help them, we must take a hard look at the policies that--intentionally or unintentionally--create the threatening environments in which these young people are growing up. This volume illuminates the challenging policy decisions that must be made. (PsycINFO Database Record (c) 2004 APA, all rights reserved).